The Effect Of Environmental And Social Factors On The Interest In Purchasing Green Products Among Generation Z In Malang City Through Green Trust As A Mediating Variable - Ronaldus Ledo; Abdul Khodir Djaelani; Ahmad Subhan Mahardani (LP2M IAIN Palopo, 2026)
The purpose of this study is to analyze the influence of environmental knowledge, environmental awareness, and social norms on the intention to purchase green products and how the mediation role of green trust as an intermediary relationship between three independent variables on the intention to purchase green products of generation Z in Malang City. The research method uses quantitative descriptive with data collection from direct questionnaire distribution and Google Form to generation Z Malang City aged 17-27 years. The sampling technique is purposive sampling with a total of 147 respondents. The data analysis technique uses PLS-SEM with the help of the SmartPLS 4.0 application. The results of this study indicate that environmental awareness and social norms have a positive influence on green trust, while environmental knowledge does not show a significant influence. Environmental knowledge, environmental awareness, and green trust have a positive influence on the intention to purchase green products, while social norms do not show a significant influence. Green trust mediates the influence of environmental awareness and social norms on the intention to purchase green products, but not on environmental knowledge. Novelty: Highlighting the mediation of green trust on social norms, enriches the TPB model. Practical implications: The Malang Government implements social media-based PLH to increase the green trust of Gen Z; Green businesses integrate social norms via influencers to encourage purchases of eco-friendly packaging and reduce urban waste.